Hikaru Noguchi's darning : repair, make, mend - Noguchi, Hikaru (Quickthorn, 2019)
This is the first UK edition of the cult darning book by Hikaru Noguchi who has become a guru of visible darning in Japan. With 12 different darning techniques and 63 inspirational examples, this detailed step by step guide makes the methods easy to follow. The stylish photography shows off the artistic and minimalist style of the designer's work.